Effects of Spiked Cylinder and Saw Band Pre-Cleaners on Trash Removal Efficiency and Fibre Properties of Cotton - Patil, P G; Shukla, S K; Manojkumar, T S (Journal of Agricultural Engineering, 2008)
A study was conducted to determine the effects of spiked cylinder and saw band pre-cleaners on trash removal efficiency and fibre properties in case of three cotton samples A, B and C having staple length 29.6, 29.0 and 25.8 mm, respectively. The trash removal efficiency and different fibre attributes of four sets of pre-cleaning operations viz., spiked cylinder cleaner, saw band cylinder cleaner, saw band cum spiked cylinder pre-cleaners and spiked cylinder cum saw band pre-cleaners were compared with control. The highest trash removal efficiencies were fOund 21.9%, 21.5% and 26.5% in spiked cylinder cleaner cum saw band pre-cleaner combination for all the three cotton aamples A, B and C, respectively whereas in case of saw band cum spiked cylinder pre-cleaners combination were 19.5%, 17.9% and 20.5% in case of saw band cleaner were 17.1%, 15.4% and 14.7%, and in case spiked cylinder pre-cleaner were 9.8%, 12.8% and 11.8%. The test results revealed that saw band cum spiked cylinder pre-cleaners combination was less effective than spiked cylinder cum saw band pre-cleaners for cleaning of all three cotton samples tested. The test result further revealed that saw band pre-cleaner was more effective in removing trash content than spiked cylinder pre-cleaner for all the three varieties of cotton tested. There was no significant difference fibre attributes in case of all the three cotton samples tested for spiked cylinder and saw band pre-cleaners.